Readiness of Scout Members in Lubuklinggau City to Perform Cardio Pulmonary Resuscitation (CPR) after CPR Training - Wibowo, Wahyu Dwi Ari; Wijaya, Sapondra; Susmini, Susmini; Soewito, Bambang (Alta Dharma Publisher, 2023)
Introduction: Even though CPR training has begun to be widely carried out, the problem of readiness of CPR training participants to carry out CPR during emergencies still needs to improve. One of the problems is the implementation of unsustainable training. There is a need to modify CPR training at a low cost so that movement can be sustainable, hoping to increase readiness. Objective: This study aimed to investigate the influence of CPR Training use of CPR Pillow on the scout member readiness in response to Hospital Cardiac Arrest (OHCA) in Lubuklinggau City, South Sumatera, Indonesia. Method: This quantitative study was conducted with a quasi-experimental approach. A total of 72 participants participated in this study, of which 36 were categorized into the experimental group and attended three CPR Training in two months by simulation method using CPR Pillow. The remaining 36 participants were in the control group and received classical CPR training using leaflets. Both the experimental and control groups were subjected to pretest and post-testing. The researcher developed a questionnaire to assess the readiness, deliberate the implementation, and conduct modifications from other studies. The Cronbach's alpha coefficients used were 0.82. The paired t-test was used to assess the data statistically. Result: The experimental group showed higher readiness progress (t = 6.834, p 0.001) than the control group. Recommendation: Continuous CPR training using CPR pillows effectively increases the readiness of training participants in dealing with OHCA victims